Analysis of the Correlation Between the Effectiveness of Subsidized Fertilizers and Farmer Welfare: The Role of Livelihood Asset Management Strategy (Case Study of Wedi, Kapas, Bojonegoro, East Java) - Nike Shelvi Yannasari; Silvana Maulidah; Riyanti Isaskar (Jurnal Penelitian Pendidikan IPA, 2024)
Most residents of Wedi village work as farmers. There are 3 farmer groups in Wedi village: Tani Makmur, Mekar Tani, and Tunas Harapan. This study aims to analyze the factors influencing the effectiveness of subsidized fertilizer distribution and to determine the correlation between the effectiveness of subsidized fertilizer distribution in increasing rice productivity in Wedi Village, Kapas District, Bojonegoro Regency. The number of samples in this study was 82 respondents measured based on the three farmer groups. The method used for analysis was SEM PLS. Data collection techniques in this study were in the form of primary and secondary data with quantitative analysis using a Likert scale. The results of the analysis showed that livelihood assets significantly influenced distribution effectiveness and farmer welfare, distribution effectiveness had a mediating effect on the correlation between livelihood assets and farmer welfare. Farmer welfare can be seen from income and the amount of farm production that can be measured in rupiah units in one season.